Тваринництво Ольвійського поліса кінця VI – першої половини III ст. до н.е. - Одрін, О.В. (Український історичний журнал, 2016)
Досліджується розвиток тваринницької галузі в Ольвійському полісі наприкінці
VI – у першій половині III ст. до н.е. Визначено рівень сприятливості природних
умов Нижнього Побужжя для різних її форм. Розглянуто галузево-територіальну структуру ольвійської хори та місце в ній спеціалізованих тваринницьких районів. Проаналізовано галузеву структуру ольвійського тваринництва. The article explores the development of animal husbandry in the polis of Olbia in the
late 6th century through the 1st third of the 3rd century BCE. It establishes whether
the natural environment of the Lower Buh river region was conducive to various forms
and branches of animal husbandry. It explores the branch and territorial structure of
the Olbian chora and the role of specialized cattle breeding regions in it. It offers an
analysis of the branches that comprised Olbian animal husbandry, and explores the
trajectories of each of its main sectors.